Preparedness of Colleges of Education in Southwestern Nigeria for the Adoption of Blended Learning - Idowu olusola Olayiwola; Kudirat Mojirade Alimi (Intelektual Pustaka Media Utama, 2015)
The study investigated the preparedness of colleges of education in Southwestern Nigeria in terms of available facilities and infrastructure for the use of blended learning. The study adopted the survey design. The population consisted of students and lecturers in colleges of education in Southwestern Nigeria. The sample size was 1,059 students and 168 lecturers. Three states were selected from which three colleges of education (one per state) also selected using the random were sampling technique. From each of the three colleges of education, 400 students and 60 lecturers were selected by stratified random sampling technique using school as stratum. Students’ Blended Learning Facilities Questionnaire, Lecturers’ Blended Learning Facilities Questionnaire and Institutions’ Blended Learning Facilities Checklist (IBLFC) were used for the study. The results showed that the institutions were not adequately prepared for blended learning as ICT facilities in the institutions were below the minimum required standard stipulated by the Federal Government of Nigeria for tertiary institutions. The study concluded that ICT facilities and infrastructure in colleges of education were inadequate for blended learning.